Similar burden of rare genetic variants in ischemic and non-ischemic dilated cardiomyopathy - Louie Cao; Joshua Rushakoff; Ian Williamson; Anja Karlstaedt; Michelle Kittleson; Lawrence Czer; Evan P. Kransdorf (Frontiers in Cardiovascular Medicine)
BackgroundThe aim of the study was to determine the prevalence of rare disease-causing variants in cardiomyopathy-associated genes in a cohort of patients with ischemic and non-ischemic dilated cardiomyopathy undergoing heart transplant.MethodsWe conducted a single-center cohort study of 60 adult patients with left ventricular ejection fraction ≤50% and left ventricular end-diastolic dimension ≥95th percentile for sex/height who underwent heart transplant between January 2017 and December 2023 and consented to participate in a cardiac tissue biobank. We evaluated the prevalence of rare (minor allele frequency <0.1%) disease-causing (pathogenic or likely pathogenic by American College of Genetics and Genomics criteria) variants in cardiomyopathy-associated genes.ResultsA total of 60 individuals fulfilled the inclusion criteria: 16 with ischemic dilated cardiomyopathy [88% men, median age 65 years, interquartile range (IQR) 64–68 years] and 44 with non-ischemic dilated cardiomyopathy (80% men, median age 53 years, IQR 39–65 years). We found that the prevalence of disease-causing variants was similar between patients with ischemic dilated cardiomyopathy (3/16 or 19%; 95% credible interval 6%–36%) and those with non-ischemic dilated cardiomyopathy (10/44 or 23%; 95% credible interval 12%–33%). Variants in the ischemic dilated cardiomyopathy group were found in the TTN and DMD genes. Variants in the non-ischemic dilated cardiomyopathy group were found in the TTN, FLNC, LMNA, MYH7, and RBM20 genes.ConclusionsPatients with ischemic dilated cardiomyopathy undergoing heart transplant possessed a similar burden of rare disease-causing variants as those with non-ischemic dilated cardiomyopathy. Our results suggest that genetic testing may be beneficial in patients with advanced heart failure requiring heart transplant due to ischemic dilated cardiomyopathy to detect disease-causing variants in cardiomyopathy-associated genes.